THE RAILWAY EDUCATION TO STUDENTS OF TK KLUMURAN 01 AND TK SUKOREJO 02 MADIUN - Puspitasari, Armyta (Education and Talent Development Center of Indonesia, 2022)
Education about railways for Kindergarten (TK) students is one way to stimulate them from their environment. Field learning activities help to explore experiences that provide opportunities for kindergarten students to know and understand the learning experiences gained from the environment by observing, imitating, and experimenting. The activities carried out were direct exploration in the field which included practicing as a machinist in a train simulator, queuing at the station entrance ticket counter, boarding an inspection train directly. Community service is located at the Indonesian Railways Polytechnic Madiun. Kindergarten students are very enthusiastic and active in participating in all series of activities. The results of the implementation of community service can be concluded: (1) Kindergarten students can improve knowledge and insight related to railways directly in the field; (2) Train the emotional intelligence of kindergarten students about discipline and railway safety, as well as a culture of order when queuing so as to train their attitudes from an early age; (3) Assist the exploration of the experiences of kindergarten students related to railways.